Cost-effectiveness of stroke care in Aboriginal and non-Aboriginal patients: an observational cohort study in the Northern Territory of Australia. Issue 10 (5th October 2017) - Zhao, Yuejen; Guthridge, Steven; Falhammar, Henrik; Flavell, Howard; Cadilhac, Dominique A
Abstract : Objective: To assess cost-effectiveness of stroke care for Aboriginal compared with non-Aboriginal patients in the Northern Territory (NT), Australia. Design: Cost-effectiveness analysis using data from a cohort-based follow-up study of stroke incidents. Setting: Public hospitals in the NT from 1992 to 2013. Participants: Individual patient data were extracted and linked from the hospital inpatient and primary care information systems. Outcome measures: Incremental cost-effectiveness ratios were calculated and assessed graphically. Survival time was used to measure effectiveness of stroke care, in comparison with the net costs per life-year gained, from a healthcare perspective, by applying multivariable models to account for time-dependent confounding. Results: 2158 patients with incident stroke were included (1171 males, 1178 aged <65 years and 966 from remote areas). 992 patients were of Aboriginal origin (46.0%, disproportionately higher than the population proportion of 27%). Of all cases, 42.6% were ischaemic and 29.8% haemorrhagic stroke. Average age of stroke onset was 51 years in Aboriginal, compared with 65 years in non-Aboriginal patients (p<0.001). Aboriginal patients had 71.4% more hospital bed-days, and 7.4% fewer procedures than non-Aboriginal patients. Observed health costs averaged $A50 400 per Aboriginal compared with $A33 700 per non-Aboriginal patient (p<0.001). The differential costs and effects for each population were distributed evenly across the incremental cost-effectiveness plane threshold line, indicating no difference in cost-effectiveness between populations. After further adjustment for confounding and censoring, cost-effectiveness appeared greater for Aboriginal than non-Aboriginal patients, but this was not statistically significant (p=0.25). Conclusions: Stroke care for the NT Aboriginal population is at least as cost-effective as the non-Aboriginal population. Stroke care presents worthwhile and equitable survival benefits for Aboriginal patients in remote communities, notwithstanding their higher level burden of disease. These findings are relevant for healthcare planning and policy development regarding equal access to stroke care for Aboriginal patients.